Lateral Suboccipital Retrosigmoid Approach with Tentorial Incision for Petroclival Meningiomas: Technical Note - Yamahata, Hitoshi (Georg Thieme Verlag KG, 2014)
Introduction The resection of petroclival meningiomas presents great neurosurgical challenges. Although multiple surgical approaches have been developed, the retrosigmoid route tends to be used to address tumors that are predominantly located in the posterior fossa. Our modification of the lateral suboccipital retrosigmoid approach with the placement of a tentorial incision yields good visualization of the supratentorial part of the tumor around the midbrain. Methods We treated four patients, one with primary and three with recurrent petroclival meningioma, by our modified approach. After lateral suboccipital craniotomy, the infratentorial part of the tumor was removed after detaching it from the tentorial surface. The cerebellar tentorium was then carefully incised from the supracerebellar angle, taking care not to damage the superior cerebellar artery and trochlear nerve. Results The operative field surrounding the midbrain was widened by this procedure, and safe dissection of the tumor from the brainstem and other neurovascular structures was performed with direct observation of the interface. Conclusions Our approach is a useful modification of the retrosigmoid approach to petroclival meningiomas. It facilitates the safe resection of the supratentorial part of the tumor in the ambient cistern behind the tentorium.